2008
DOI: 10.1111/j.1365-2443.2008.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities in the developmental status of embryo‐derived stem cells and primordial germ cells revealed by global expression profiling

Abstract: Embryonic germ‐line cells are unipotent cells that give rise to either sperm or oocytes. However, pluripotent stem cells can be derived from primordial germ cells (PGCs) or spermatogonia, suggesting that germ‐line cells retain a capacity for pluripotency. Here, we made genome‐wide comparisons of the gene expression profiles of freshly isolated PGCs, in vitro‐formed PGCs (iPGCs), and other stem cell lines, including embryonic stem cells (ESCs), embryonic germ cells (EGCs) and germ‐line stem (GS) cells. Comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 55 publications
(119 reference statements)
3
39
0
Order By: Relevance
“…6). It has been reported that transcriptome characteristics of PGCs are different from those of pluripotent cells [38]. Our microarray data uncovered the sequential changes in transcription during the conversion of PGCs to pluripotent cells.…”
Section: Pluripotent Candidate Cells Progress S Phase Of Cell Cycle Amentioning
confidence: 64%
“…6). It has been reported that transcriptome characteristics of PGCs are different from those of pluripotent cells [38]. Our microarray data uncovered the sequential changes in transcription during the conversion of PGCs to pluripotent cells.…”
Section: Pluripotent Candidate Cells Progress S Phase Of Cell Cycle Amentioning
confidence: 64%
“…In line with this notion, micro-array analyses have shown that many "PGC signature" genes (i.e. Dazl, Mvh and developmental pluripotency-associated protein 2, Dppa2) were not fully up-regulated in putative PGCs obtained from Mvh-LacZ or Mvh-GFP knock-in mouse ESCs (Mise et al, 2008).…”
Section: Discussionmentioning
confidence: 90%
“…In those studies, however, the latest developmental stage analyzed was 10.5 dpc, identifying genes expressed very early during PGC development. Two microarray experiments have analyzed the transcriptomes of male and female germ cells isolated at 11.5, 12.5, and 13.5 dpc [30] or of pooled XX and XY germ cells isolated at 10.5 and 12.5 dpc [29], yielding potential insights into early germ cell differentiation events. However, because these studies did not include somatic controls, they did not identify germ cell-specific genes.…”
Section: Methodological Considerations and Comparisons To Previous Stmentioning
confidence: 99%